Analisis Perhitungan Tenaga Kerja pada Produksi Rambut Palsu (Studi Kasus : CV. Mahkota Kreasi Berlina) - Insani, Alif Beta Mulya; Khoiroh, Siti Muhimatul (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
CV. Mahkota Kreasi Berlina is struggling to keep up with demand. Even though currently, CV Mahkota Kreasi Berlina has added working hours every week. In this case CV. Mahkota Kreasi Berlina has never carried out a workforce optimization calculation and made a comparison of additional workers with overtime hours. therefore, in order to meet demand, researchers will calculate the need for labor and make a comparison between adding labor and overtime according to production planning or with the workload analysis (WLA) method at the minimum cost. From the results of data processing, the minimum cost results are obtained, namely the calculation of the number of labor requirements in a 6 month period using 42 workers and overtime with a total cost of Rp. 495,800,000 per 6 months. Calculation of labor with WLA resulted in the company incurring substantial costs, where the results of the calculation of WLA amounted to Rp. 526,392,533 per 6 months